Information and Service Support of the Mechanism of Industry Functioning in the Single Digital Space - O. V. Loseva; N. M. Abdikeev (Управленческие науки)
The functioning of industry in the context of the creation and development of a single digital space of the Russian economy requires the development of an appropriate mechanism, in which information and service support for the digitalization of business processes of industrial enterprises should play a key role. The purpose of this study is to build a model of the mechanism for the functioning of an industrial enterprise in a single digital space (hereinafter referred to as the SDS) as well as to characterize the information and service support for the control and governing functions of this mechanism. The categorical apparatus of the digital economy and digital technologies, methods of classification, comparative analysis, functional and systemic approaches were used as the methodological basis of the study. The results of the work were the construction of a conceptual model of the mechanism of functioning of an industrial enterprise in a single digital space, based on the principle of optimality and capable of adapting to the needs of a particular industrial enterprise, as well as the identification of the basic functions of the management activity of an industrial enterprise in the single digital space, and the characteristics of the information and service support mechanism, which is digital services (technologies) that ensure management activities and interaction of actors of the business ecosystem in the single digital space. The conclusions drawn from the results of the study can be applied in practice by the management of companies when developing their own mechanism and strategy for digitalizing business processes in order to increase the efficiency of functioning in the single digital space industry.